To find an equivalent expression for \( 9x^2 - 25 \) using the Distributive Property, we can recognize that this expression is a difference of squares. The difference of squares can be factored using the formula:
\[ a^2 - b^2 = (a + b)(a - b) \]
In this case:
- \( a^2 = 9x^2 \) which implies \( a = 3x \)
- \( b^2 = 25 \) which implies \( b = 5 \)
So, we can rewrite \( 9x^2 - 25 \) as:
\[ (3x)^2 - 5^2 \]
Using the difference of squares formula:
\[ 9x^2 - 25 = (3x + 5)(3x - 5) \]
Among the response options given, the equivalent expression is:
\[ (3x + 5)(3x - 5) \]
So the correct answer is:
(3x+5)(3x−5)